2010
DOI: 10.15835/nsb234772
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bioagents and Biopesticides against Colletotrichum lindemuthianum and its Integrated Management in Common Bean

Abstract: Three bioagents (Trichoderma viride, T. harzianum and Gliocladium virens) and five biopesticides (Achook, Neemgold, Wannis, Spictaf and Neemazal) were evaluated under in vitro and in vivo conditions against Colletotrichum lindemuthianum. All the three antagonistic fungi caused significant inhibition of mycelial growth, maximum being with T. viride (69.21%) followed by T. harzianum (64.20%). Among the biopesticides tested at four concentrations, Wanis applied @ 1000 µl/ml caused maximum inhibition of 82.12 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…The highest growth of mycelia (3.4 cm) was measured from the control, whereas the least (0.67 cm) was from the dual culture containing T. viride (Table 1; Figure 3). This is similar to the works of Padder et al (2010) who, in India, recorded mycelia growth inhibition of 69.21 and 64.2% with T. viride and T. harzianum, respectively, against a local strain of C. lindemuthianum.…”
Section: Antifungal Assaysupporting
confidence: 91%
See 2 more Smart Citations
“…The highest growth of mycelia (3.4 cm) was measured from the control, whereas the least (0.67 cm) was from the dual culture containing T. viride (Table 1; Figure 3). This is similar to the works of Padder et al (2010) who, in India, recorded mycelia growth inhibition of 69.21 and 64.2% with T. viride and T. harzianum, respectively, against a local strain of C. lindemuthianum.…”
Section: Antifungal Assaysupporting
confidence: 91%
“…Siderophore production by different Trichoderma strains is documented (Heidrun et al, 1991). Padder et al (2010) suggested a hyphal interaction mechanism in which hyper parasitism along with the production of antibiotics and secondary metabolites like siderophores to have contributed to the inhibition of mycelial growth, and control of seed borne infection.…”
Section: Siderophore Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the co-formulation of metalaxyl and mancozeb (Mancolaxyl 72 WP), which resulted in satisfactory control of Colletotrichum coccodes on tomatoes, was found to be a good option to prevent fungicide resistance (Johnston, 1986). It has been reported that seed dressing or soil application of bioagents like Trichoderma viride, Trichoderma harzianum and Gliocladium virens caused significant inhibition of mycelial growth of C. lindemuthianum, thereby effectively controlled the seed borne infection and increased the seed germination of common bean (Padder et al, 2010). Extracellular metabolites like siderophores, antibiotics, lytic enzymes and volatile compounds produced by rhizobacteria (Pseudomonas fluorescens and Bacillus cepacia) have also been reported to effectively reduce lesions and damages caused by C. lindemuthianum on bean plants (Hernandez et al, 2004).…”
Section: Original Researchmentioning
confidence: 99%
“…Necrotic lesions can also be observed on the upper leaf surface and on the petioles. On the pods, the presence of medium lesions are evident but also some small and large lesions generally with sporulation and that cover approximately 10% of the pod's surface area may be found and 9= more than 25% of the leaf surface area covered with large coalescing and generally necrotic lesions resulting in defoliation (Sharma, 2010).…”
Section: Anthracnose Disease Assessmentmentioning
confidence: 99%